Emerging Issues in Green Criminology
IX, 265 p.
Keywords: This edited collection brings together internationally renowned scholars to explore green criminology through the interdisciplinary lenses of power, harm and justice. The chapters provide innovative case study analyses from around the world that seek to advance theoretical, policy and practice discourses about environmental harm.